2017
DOI: 10.1002/crat.201600335
|View full text |Cite
|
Sign up to set email alerts
|

Structural, optical, and magnetic properties of Cu‐doped TiO2 samples

Abstract: We report here the microstructure, optical, and magnetic properties of Cu-doped TiO 2 (Ti 1−x Cu x O 2 ) nanopowder samples with x = 0.02, 0.04, and 0.06 prepared by a solid-state reaction method. XRD studies indicated the incorporation of Cu into the TiO 2 lattice. Ultraviolet-visible spectroscopy (UV-vis) measurements revealed that the band gap decreased due to the incorporation of Cu. Photoluminescence (PL) results showed an enhanced photoluminescence property associated with oxygen vacancies from TiO 2 due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…In addition, the photocurrent response of CuSA-TiO 2 shows high reproducibility and stability for several on/off cycles. Moreover, the electrochemical impedance spectra (EIS) were used to study the transfer properties of charge carriers 46 , as indicated in Supplementary Fig. 16b .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the photocurrent response of CuSA-TiO 2 shows high reproducibility and stability for several on/off cycles. Moreover, the electrochemical impedance spectra (EIS) were used to study the transfer properties of charge carriers 46 , as indicated in Supplementary Fig. 16b .…”
Section: Resultsmentioning
confidence: 99%
“…The EIS spectra were used to study the transfer properties of charge carriers, 26 as indicated in Fig. 5(c).…”
Section: Resultsmentioning
confidence: 99%
“…Aluminates have been widely used as dyes and pigments due to their structural arrangement in the spinel form (A 2+ B 2 3+ O 4 2− ) that allows the insertion of chromophore ions, which guarantee intense color and high thermal stability, in addition to resistance to chemically aggressive environments. 15,16 The synthetic routes most used to obtain aluminates are coprecipitation, 17 mixed oxide calcination, 18 solid-state reactions, 19 and the sol–gel method. 20 In addition, there is the possibility of recycling aluminum to be used as a pigment precursor, 17 providing a more sustainable synthesis compatible with the circular economy concept, which is based on reducing, repairing, recycling, remanufacturing, and redirecting the materials life cycle, 21,22 contributing to the production of more sustainable materials.…”
Section: Introductionmentioning
confidence: 99%